MENGEMBANGKAN KEMAMPUAN MENGENAL KONSEP BILANGAN ANAK USIA DINI MELALUI MEDIA KERETA ANGKA DI GAMPONG KRUENG ANOI KUTA BARO ACEH BESAR - Susi Kamisna; Israwati .; Yuhasriati .; Taat Kurnita Yeniningsih; Rahmi . (Jurnal Ilmiah Mahasiswa Pendidikan Anak Usia Dini, 2022)
Keywords: Recognizing the Concept of Numbers, Number Train Media, Early ChildhoodThe level of developmental achievement of children aged 5-6 years can mention the symbols of numbers 1-10, using number symbols to count and match numbers with number symbols. The purpose of this study was to determine the ability to recognize the concept of numbers in early childhood through the number train media in Krueng Anoi Village, Kuta Baro, Aceh Besar. The approach used in this study was a qualitative research approach with descriptive analysis. The subjects in this study were children aged 5- 6 years in Krueng Anoi Village, Kuta Baro, Aceh Besar. The data collection technique in this study used observation, performance and interviews. It is known that from the activities of children playing through the number train media to develop the ability to recognize the concept of numbers, the results obtained that the six research subjects on average were in the Very Good Developing assessment indicator (BSB). if the child has developed 3 aspects of 3 aspects of development, namely mentioning the symbols of numbers 1-10; Matching numbers with number symbols and recognizing the concept of numbers. After doing research on each research subject, it can be concluded that the ability to recognize the concept of numbers for early childhood can develop through the number train media. Playing activities with the number train media are recommended to be applied to children aged 5-6 years in order to improve the ability to recognize the concept of numbers in early childhood. Abstrak. Penelitian ini bertujuan untuk mengetahui kemampuan mengenal konsep bilangan anak usia dini melalui media kereta angka di Gampong Krueng Anoi Kuta Baro Aceh Besar. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan penelitian kualitatif dengan analisis deskriptif dengan subjek penelitian anak usia 5-6 tahun di Gampong Krueng Anoi Kuta Baro Aceh Besar. Data diperoleh melalui observasi, unjuk kerja dan wawancara. Hasil penelitian menunjukkan bahwa pembelajaran yang dilaksanakan di Gampong Krueng Anoi Kuta Baro Aceh Besar adalah pembelajaran daring menggunakan aplikasi whatsApp berupa vidio dan foto yang dikirimkan oleh orang tua yang kemudian peneliti melakukan pengamatan pada anak untuk memperoleh data sejauh mana perkembangan kemampuan anak dalam mengenal konsep bilangan melalui media kereta angka yaitu menyebutkan lambang bilangan 1-10; mencocokkan bilangan dengan lambang bilangan dan mengenal konsep bilangan.Kata Kunci: Mengenal Konsep Bilangan, Media Kereta Angka, Anak Usia Dini